Adherence, Medical Outcomes, and Health Care Costs in Adolescents/Young Adults Following Pediatric Liver Transplantation. Issue 2 (February 2020) - Lawrence, Zoe E.; Martinez, Mercedes; Lobritto, Steven; Chen, Justin; Breslin, Nadine; Fox, Alyson; Vittorio, Jennifer
ABSTRACT: Objective: Improved outcomes after pediatric liver transplantation (LT) have led to increasing numbers of adolescent and young adult recipients entering into adult health care systems. The aim of this study was to evaluate the impact of transition from pediatric to adult health care models on medical outcomes, measures of adherence, and health care utilization for pediatric LT recipients. Methods: We evaluated the course of patients who received an LT while followed in pediatrics and transferred to an adult care provider within our institution. Data were collected from 2 years preceding and 2 years following transfer of care. Results: A total of 32 patients were eligible for analysis. Median age at time of transfer was 22.9 years (interquartile range 21.7–23.6). Nine patients (28%) died following transfer of care. There was a significant decrease in office visit adherence following transfer of care ( P  = 0.02). Although not achieving significance, an increase in alanine aminotransferase values, episodes of acute cellular rejection, progression to cirrhosis, evolution to chronic rejection, and hospital admission rates post transfer were found. These findings were associated with an increase in health care costs related to required interventions. Conclusions: Our study demonstrates trends toward worse health outcomes, decreased adherence, and increased health care utilization following transfer of care. These findings and poor patient survival suggest that the time around transition from pediatric to adult health care models represents a period of increased vulnerability for pediatric LT recipients. Larger, multicenter, prospective studies are needed to identify factors and interventions that affect adolescent and young adult to improve the transition process.